Exploring the influential factors of continuance intention to use mobile apps : extending the expectation confirmation model - Santos, Diogo Manuel Leitão Vinagre Piteira dos (2017)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence